2005
DOI: 10.1093/humrep/deh625
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human LH supplementation versus recombinant human FSH (rFSH) step-up protocol during controlled ovarian stimulation in normogonadotrophic women with initial inadequate ovarian response to rFSH. A multicentre, prospective, randomized controlled trial

Abstract: rLH supplementation is more effective than increasing the dose of rFSH in terms of ovarian outcome in patients with an initial inadequate ovarian response to rFSH alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 20 publications
4
90
0
2
Order By: Relevance
“…It has been suggested that rLH supplementation is effective in young, normogonadotrophic patients who demonstrate a suboptimal ovarian response to initial rFSH stimulation [6] or who had required high doses of rFSH in a previous cycle [12]. Unfortunately, we are unable to determine the number of 'suboptimal responders' within our study group to perform such a subgroup analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been suggested that rLH supplementation is effective in young, normogonadotrophic patients who demonstrate a suboptimal ovarian response to initial rFSH stimulation [6] or who had required high doses of rFSH in a previous cycle [12]. Unfortunately, we are unable to determine the number of 'suboptimal responders' within our study group to perform such a subgroup analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Specific populations that have been suggested to benefit include patients greater than 35 years of age [1,13,14,16], suboptimal responders to ovarian stimulation ( [6,12,16]) and those undergoing specifically a GnRH antagonist cycle [2] or GnRH agonist cycles [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, in women above 35 years of age, poor responders, or with more severe pituitary GnRH-a suppression, stimulation with r-LH in the mid/late-follicular phase could be associated with improved results [6,12,24,34,37,40,41,47]. In a recent meta-analysis study it has been suggested that the supplementation with r-LH in patients of advanced reproductive age stimulated with r-FSH, may improve implantation and clinical pregnancy without affecting metaphase II (Met II) yield [31].…”
Section: Introductionmentioning
confidence: 99%
“…Ancak sadece poor responder kadınları içeren çalışmalarda r-LH eklenmesiyle gebelik oranlarında anlamlı artış olduğunu göstermiştir. 25,27 Yine 2011 yılında Bosch ve ark.nın GnRH antagonist protokol uygulanan olgular üze-rinde yaptıkları çalışmada 36-39 yaş grubundaki olgularda r-LH eklenmesinin implantasyon oranını ve devam eden gebelik oranlarını artırdığı, 36 yaşın altındaki olguların LH desteğinden fayda görme-diklerini bildirmişlerdir. 28 Sonuç olarak, KOS'ta seçilmemiş olgularda r-LH eklenmesinin faydası olmadığı görülmektedir.…”
Section: Gonadotropi̇n Seçi̇mi̇unclassified